Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Puskesmas Maek - Anisa Wulandari; Dori Mittra Candana; Deni Saputra (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of organizational culture and communication on employee performance with job satisfaction as an intervening variable at Maek Public Health Center, Lima Puluh Kota Regency. This study employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to all employees of Maek Public Health Center, totaling 50 respondents. The data analysis technique used in this study is Structural Equation Modeling (SEM) with SmartPLS 4, while data collection was conducted using questionnaires measured on a Likert scale. The results of the study indicate that organizational culture and communication have a positive and significant effect on employee performance. Furthermore, communication has a positive and significant effect on job satisfaction, whereas organizational culture does not have a significant effect on job satisfaction. Job satisfaction is proven to have a positive and significant effect on employee performance. The indirect effect analysis shows that job satisfaction is not able to mediate the effect of organizational culture on employee performance, but it is able to mediate the effect of communication on employee performance. This indicates that effective communication can improve employee job satisfaction, which in turn enhances employee performance, while organizational culture has a more direct effect on employee performance without being mediated by job satisfaction.